Understanding same-sex relationships in gay individuals - Tanvi Malick; Aarzoo Gupta; Priti Arun (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: The social demands and pressure often lead individuals of the sexual minority to enter heterosexual marriages resulting in the termination of ongoing same-sex relationships. Consequently, short-lived relations and multiple romantic or sexual partners. Methods and Material: The study aimed to assess couple satisfaction in relation to sexual satisfaction, mental health, and stigma in gay individuals. It was a correlational cross-sectional study conducted online through social media platforms using Google Forms. The assessment measures used were: Couple Satisfaction Index, New Sexual Satisfaction Scale, General Health Questionnaire, and Self-Stigma Scale. Out of a total of 115 posts, 92 responses were received from which a sample of 30 was analyzed using Statistical Package for the Social Sciences version 28. Descriptive statistics, Spearman's correlation, and regression were computed to determine predictors of relationship satisfaction. Results: The correlation between sexual satisfaction and couple satisfaction (r = 0.52, P ≤0.01) was significant indicating that sexual satisfaction increases couple satisfaction. Psychological distress and stigma were inversely related to couple satisfaction but not to sexual satisfaction. Conclusions: Sexual satisfaction largely determined the couple's satisfaction while psychological distress or stigma accounts for a small percentage of couple satisfaction.